Local Tuberculosis Georeference: a tool to define BCG vaccination in high-incidence area in Portugal. (13th November 2019) - Freire Rodrigues, E; Leite, A; Cabral, M; Duarte, G; Marques, A P; Cale, E; Silva, A C
Abstract: Issue: Tuberculosis (TB) incidence in Portugal is < 20/100000 people, with high-incidence municipalities in urban areas such as Amadora. In 2016, the national vaccination programme moved the BCG vaccine from universal to restricted risk groups. Amadora, due to the higher-incidence area, maintained a universal vaccination policy. Recently, it was hypothesized that vaccination could be applied to specific parishes even in high incidence counties. Description: We aimed to identify specific geographic areas with higher risk of TB to help redefine the local BCG vaccination policy. We proposed to georeference active TB cases between 2015 and 2017, in Amadora, to then assess the incidence per parish and statistical section. We also aimed at identifying geo-clusters and density of cases. Methods: (1) notified TB cases from 1 January of 2015 to 31 December 2017 were extracted from TB surveillance system; (2) cases of latent TB infection (LTBI), cases out of Amadora's bounds and without national ID were excluded; (3) ArcGis®Online and associated maps were used to provide populational estimates; (4) cumulative incidence was calculated per year and averaged for the 3-year period; (5) Clusters were determined using distance and simple density of cases was calculated using Kernel algorithm. Results: Considering the 6 parishes of Amadora, the 3-year cumulative incidence varied from 19.58 to 38.3 per 100000 hab. The highest incidence was found on the parish with the best socio-economic profile. 14 geo-clusters were mapped; 3 matched known deprived neighborhoods. Overall density was higher in these neighborhoods. Lessons: With this approach we found that deprived neighborhoods had higher levels of case density, but 3-year cumulative incidence was higher on the parish considered to have low occurrence of TB. As such, and due to the intense population flows in Amadora, the local public health unit recommended the persistence of BCG vaccination to all residents of the municipality. Key messages: Georeferecing supported our recommendation to mantain a universal BCG vaccination policy. Georeferencing associated to surveillance systems is highly useful to ensure evidence based public health practices, even at the local level.